The role of tumor microenvironment reprogramming in primary liver cancer chemotherapy resistance - Zhao, Chunyu; Liu, Shanshuo; Gao, Feng; Zou, Yawen; Ren, Zhigang; Yu, Zujiang (Frontiers in Oncology, 2022)
Primary liver cancer (PLC), including hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC), and other rare tumours, is the second leading cause of cancer-related mortality. It has been a major contributor to the cancer burden worldwide. Of all primary liver cancer, HCC is the most common type. Over the past few decades, chemotherapy, immunotherapy and other therapies have been identified as applicable to the treatment of HCC. However, evidence suggests that chemotherapy resistance is associated with higher mortality rates in liver cancer. The tumour microenvironment (TME), which includes molecular, cellular, extracellular matrix(ECM), and vascular signalling pathways, is a complex ecosystem. It is now increasingly recognized that the tumour microenvironment plays a pivotal role in PLC prognosis, progression and treatment response. Cancer cells reprogram the tumour microenvironment to develop resistance to chemotherapy drugs distinct from normal differentiated tissues. Chemotherapy resistance mechanisms are reshaped during TME reprogramming. For this reason, TME reprogramming can provide a powerful tool to understand better both cancer-fate processes and regenerative, with the potential to develop a new treatment. This review discusses the recent progress of tumour drug resistance, particularly tumour microenvironment reprogramming in tumour chemotherapy resistance, and focuses on its potential application prospects.